Factors of Specialized Mental Health Care Use in the Netherlands: A Scoping Review Applying Andersen-Newman's Care Utilization Model - Daphne Aimée Van der Draai; Erik Van Duijn; Derek Paul De Beurs; Anika Bexkens; Aartjan Theodoor Frans Beekman (SAGE Publishing, 2021)
As mental disorders impact quality of life and result in high costs for society, it is important patients receive timely and adequate care. This scoping review first aims to summarize which factors contribute to specialized mental health care (SMHC) use. Within the Dutch health care system, the general practitioner (GP) is the filter for SMHC and care use costs are relatively low. Second, to organize factors by Andersen and Newman's care utilization model in illness level, predisposing, and enabling factors. Third, to assess equity of access to SMHC in the Netherlands. A health care system is equitable when illness level and the demographic predisposing factors age and gender account for most variation in care use and inequitable when enabling factors and social predisposing factors such as education predominate. We identified 13 cross-sectional and cohort studies in the Netherlands published between 1970 and September 2020 with 20 assessed factors. Illness level factors, disease severity, diagnosis, personality, and comorbidity contributed the most to SMHC use. Predisposing factors related to a more solitary lifestyle contributed to a lesser degree. Enabling factors income and urbanicity contributed the least to SMHC use. These results imply inequity. Factors that did not fit the care utilization model were GP related, for example the ability to recognize mental disorders. This emphasizes their importance in a system where patients are dependent on GPs for access to SMHC. Focus should be on improving recognition of mental disorders by GPs as well as collaboration with mental health care professionals.